Analisis Nilai-Nilai Filsafat Rasionalisme dalam Buku Fahruddin Faiz - Bagus Astaman, Raden (UIN Sumatera Utara, 2024)
Philosophy is a subject of study that is widely discussed. Many philosophical texts attract attention. One Muslim scholar who has written many books on philosophy, namely Dr. Fahruddin Faiz, one of the books that talks about rationalism is a book entitled